PERISTIWA DAN LATAR BELAKANG KERUSUHAN ANTAR SUKU MADURA-MELAYU DI KECAMATAN PEMANGKAT, KABUPATEN SAMBAS PADA TAHUN 1999 - Bayu Bestari; Amrazi Zakzo; Haris Firmansyah (Universitas Tanjungpura, 2022)
AbstractThe riots that occurred in Sambas Regency were a fairly large riot in the history of theconflict in Indonesia involving the Malays and the Madurese. Pemangkat sub-district isone of the sub-districts experiencing severe conflict. The riots that occurred inPemangkat District were motivated by riots that occurred in Jawai District and also inTebas District. The riots that occurred caused many Madurese residents to becomevictims and had to evacuate themselves out of town. This article aims to explain thechronology and background of the riots between the Madurese-Malay tribes inPemangkat sub-district in 1999 using historical research methods, namely topicselection, heuristics, verification, interpretation, and historiography. From thediscussion about the incident and the background of the riots between the Madura-Malaytribes in this article, it will be concluded that the riots that occurred in PemangkatDistrict were motivated by riots that occurred in several sub-districts in Sambas Regencyand chronologically how the riots occurred in Pemangkat District in year 1999.Keywords: Riot, Pemangkat District, Madura Tribe, Malay Tribe